Second-dose measles vaccination coverage and associated factors among children aged 19 to 35 months in Debre Birhan city, Ethiopia, 2024: A community-based cross-sectional study - Tebabere Moltot; Zenebe Abebe Gebreegziabher; Agmasie Damtew Walle; Mistire Nigussie; Micheal Amera Tizazu; Addisalem Workie Demsash; Eyosias Yeshialem (PLoS ONE, 2026)
Background Achieving high coverage of both measles vaccine doses is essential for herd immunity. Despite high first-dose coverage, measles outbreaks persist in Debre Birhan City, Ethiopia. Therefore, this study aimed to assess second-dose measles vaccine coverage.and its associated factors among children aged 19–35 months in Debre Birhan City, Ethiopia. Methods A community-based cross-sectional study was carried out in Debre Birhan City from May 10–30, 2024. Systematic random sampling method was used to recruit 626 children aged 19–35 months. Data were collected through a pre-tested, interviewer-administered questionnaire using Kobo Toolbox and later analyzed with SPSS-25. Bivariable and multivariable logistic regression analyses were performed, with statistically significant factors identified at a 95% confidence interval and a p-value of less than 0.05 in the multivariable analysis. Results A total of 626 children participated in the study, achieving a 98.7% response rate. The second-dose measles vaccination coverage among children aged 19–35 months in Debre Birhan City was 57.3% (95% CI: 53.5–61.2). Significant factors associated with the second-dose of measles vaccination coverage were: father’s education level: primary (AOR: 1.63; 95% CI: 1.17–3.69), secondary (AOR: 2.04; 95% CI: 1.83–7.01), and college or above (AOR: 3.2; 95% CI: 1.5–6.95). Other significant predictors were the child being vaccinated for any vaccine (AOR: 3.04; 95% CI: 1.33–6.98), having canceled or postponed vaccination schedules (AOR: 4.9; 95% CI: 2.62–9.32), good level of awareness (AOR: 3.3; 95% CI: 2.12–5.17), and high level of perception (AOR: 5.1; 95% CI: 3.16–8.20). Conclusion Second-dose measles vaccination coverage in Debre Birhan City is lower than the national and global target. Key factors influencing coverage include the father’s educational level, canceled or postponed vaccination schedules and caregivers’ awareness and perception of measles vaccination. Therefore, to improve coverage, it is essential to strengthen health education, streamline vaccination schedules, and enhance communication with parents.